Simulation of the solution of a viscous porous medium equation by a particle method - Oelschläger, Karl (SIAM journal on numerical analysis, 2006)
To solve a particular partial differential equation, namely a viscous porous medium equation, we discuss a particle method, which is based on the concept of moderately interacting many-particle systems. Our approach may be classified as a combination of a smoothed particle hydrodynamics method and a particle-mesh method. Quantitatively, it is assessed in terms of estimates on the approximation error.